Greedy Intersection-Mode Routing Strategy Protocol for Vehicular Networks - Marwan Mahmoud; Mahmoud Ahmad Al-Khasawneh (Complexity)
The advantages of vehicular ad hoc networks (VANETs) have been acknowledged, particularly during the last decade. Furthermore, VANET-related issues have been addressed by different researchers. Forwarding information professionally in a VANET is considered a challenging task precisely at the intersections where forwarding the information turns out to be extremely problematic. To elucidate this problem, many researchers have established routing protocols. The improved greedy perimeter stateless routing protocol (IGPSR) has been suggested, in the direction of employing greedy-mode proceeding traditional transportation's streets as well as to employ intersection-method at the joints. In view of greedy mode, the selection of the following stage is as in GPSR. By contrast, in the mode at an intersection, we would expect the vehicle guidelines to govern the following stage. The recreated consequences expose the algorithm, which is anticipated to undeniably demonstrate its competency.